Estimation of central tendency, dispersions and correlations of growth traits in Rambouillet sheep - , ANAMIKA; CHAKRABORTY, D.; AZHAR, PEER MOHD; SUDAN, AAKRITI; AZAD, MANDEEP SINGH (Indian Journal of Animal Production and Management, 2017)
Data on growth traits of 7161 animals used in present study were collected from the history sheets ofRambouillet sheep maintained at Government Sheep Breeding Farm, Reasi, J&K, India. Growth traitsincluded in the study were birth weight (BW), three-month weight (3MW), six-month body weight (6MW),nine-month body weight (9MW) and twelve-month body weight or yearling weight (YW). The averageweight gain of individual during 0-3 months (ADG1), 3-6 months (ADG2), 6-9 months (ADG3), 9-12months (ADG4) and 3-12 months (ADG5) were calculated as weight gain during particular period dividedby duration of that period in days. The overall averages were 3.39±0.01kg, 14.16±0.03kg, 19.59±0.04kg,24.85±0.05kg and 28.71±0.06kg, respectively for BW, 3MW, 6MW, 9MW and YW. The overall averageswere 0.119±0.002kg, 0.071±0.001kg, 0.058±0.006kg, 0.056±0.001kg and 0.054±0.001kg, respectively forADG1, ADG2, ADG3, ADG4 and ADG5. Sex had significant effect on all growth traits under study exceptfor 9 MW, where sex had non-significant. For growth rate traits sex had non-significant effect for ADG1 andADG4. The correlation coefficients of between different body weights and average daily weight gain rangesfrom -0.040±0.01 between ADG1 & ADG5 to 0.97±0.01 between BW and 9W. Most of the correlationsvalues were highly significant barring few exceptions, which indicate improvement of one trait will resultin improvement of other traits also. Low to medium coefficient of variations (CV) for growth traits indicatecollateral selection will be effective for improvement of growth traits.